As medidas estruturantes e a legitimidade democrática do Supremo Tribunal Federal para sua implementação - Jobim, Marco Félix (2012)
The country needs a Judicial Branch that makes its decisions effective. That is the main concern and the ground from which this doctoral thesis stems, which thesis studied some of the major cases heard by the Supreme Court of the United States of America and the reason why, in one of the most controversial decisions in the Court s history, said court resolved to, via a series of measures, carry out a decision which apparently lacked the grounds to be actualized. It is the case Brown v. Board of Education of Topeka, in which the Court, by breaking the hundred year-old cultural paradigm of a doctrine called separate but equal, authorized a black girl to attend a public school for whites as their equal. The decision by itself would have languished on the shelves of court files had not the Supreme Court, in this case, designed a more activist system in which the judge is authorized to carry out a court decision. From that standpoint and to design a potential Brazilian system, this thesis brings the ideas of Yale University professor Owen Fiss, who first used the term structural reform to refer to that type of judicial activism.It then becomes clear that this thesis turns to comparative law for a solution, and takes from the North-American doctrine a concept we believe can be implemented in Brazil. Next, the author discusses a few Brazilian Federal Supreme Court decisions which should resort to the doctrine addressed herein. In addition to that, the author states that structural reform cannot be carried out regarding every single case but solely with respect to those decisions whose elements somehow break the cultural paradigm existing in society, and it may step into legislative and even executive roles as there is a democratic foundation for such purpose, as is also advocated in labor